2011
DOI: 10.1590/s0103-863x2011000100003
|View full text |Cite
|
Sign up to set email alerts
|

O autoconceito de adolescentes escolares

Abstract: Este estudo objetivou identificar e comparar o autoconceito dos adolescentes escolares de uma amostra da cidade de João Pessoa-PB, Brasil, associado às variáveis sexo, faixa etária e tipo de escola frequentada (pública ou privada). Para tanto foi utilizado o Inventário dos Esquemas de Gênero do Autoconceito em 686 adolescentes estudantes. De modo geral, os adolescentes apresentaram autoconceito positivo, variando em função do sexo (maior para o feminino), idade (quanto menor a idade, maior a percepção negativa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…Some authors 51,52 have found that self-concept varies according to age, suggesting that it is stable during childhood, declines during adolescence and increases in early adulthood due to greater self-acceptance. A study 53 with 686 school children in the State of Paraíba that explored the association between self-concept and sex, age, and type of school attended (state or private) showed that participants had positive self-concept. The findings also showed that self-concept varied according to sex (greater in girls), age (in boys, the lower the age, the greater negative self-perception, while among girls the prevalence of negative self-perception was greatest in the 16 to 18 years age group), and type of school (self-concept was more positive among teenagers attending state schools).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors 51,52 have found that self-concept varies according to age, suggesting that it is stable during childhood, declines during adolescence and increases in early adulthood due to greater self-acceptance. A study 53 with 686 school children in the State of Paraíba that explored the association between self-concept and sex, age, and type of school attended (state or private) showed that participants had positive self-concept. The findings also showed that self-concept varied according to sex (greater in girls), age (in boys, the lower the age, the greater negative self-perception, while among girls the prevalence of negative self-perception was greatest in the 16 to 18 years age group), and type of school (self-concept was more positive among teenagers attending state schools).…”
Section: Discussionmentioning
confidence: 99%
“…Desse modo, as variáveis que representam a visão positiva de si conseguiram prever negativamente a maioria das variáveis de desfecho (afetividade negativa), sendo a autoeficácia a variável mais frequente em termos de predição. que autoestima e autoeficácia são componentes do autoconceito geral, e outros que são totalmente diferentes (Harter, 1990;Saldanha et al 2011;Wilgenbusch & Merrell, 1999), essa força de correlação pode ser um indicativo de que maiores investigações devem ser feitas para entender, conceituar e/ou diferenciar esses construtos.…”
Section: Resultsunclassified
“…Por fim, a autoestima se refere a uma avaliação subjetiva que o indivíduo faz de seu valor como pessoa, do quão satisfeito ele está com sua autoimagem, ou seja, com seu corpo e jeito de ser (Orth & Robins, 2019). Alguns estudos consideram que a autoestima e a autoeficácia são componentes do autoconceito, outros acreditam que, apesar da similaridade, eles se diferem em termos de compreensão e avaliação (Harter, 1990;Saldanha et al, 2011;Wilgenbusch & Merrell, 1999).…”
Section: Introductionunclassified
“…O período da adolescência é importante por ser fase caracterizada por inúmeras mudanças físicas e psicológicas 2,6 , que influenciam diretamente na autoestima e no autoconceito físico 6,24 . Crianças e adolescentes com baixa autoestima são mais suscetíveis a apresentarem episódios de autolesões 25 e sintomas depressivos 26 .…”
Section: Introductionunclassified